ПЛАЗМОГРАФИЧЕСКАЯ ИНДИКАЦИЯ ПАТОЛОГИЧЕСКИХ СТРУКТУР БИОПЛАЗМЫ ЧЕЛОВЕКА(ОПЫТ РАБОТЫ) (Experimental biology, 2015)
Plazmographic registration of bioplasma body of the person defects is applied for revelation of early displays of the future diseases as well as definition of severity level of existing pathological processes, including the population suffered from nuclear tests.
Keywords: f bioplasma body; pathological processes